On a dubious theory of cross-country differences in intelligence - Kevin Denny (University College Dublin, UCD School of Economics, 2009)
Kanazawa (2007) offers an explanation for the variation across countries of average intelligence. It is based on the idea human intelligence is a domain specific adaptation and that both temperature and the distance from some putative point of origin are proxies for the degree of novelty that humans in a country have experienced. However the argument ignores many other considerations and is a priori weak and the data used questionable. A particular problem is that in calculating distances between countries it implicitly assumes that the earth is flat. This makes all the estimates biased and unreliable.
hdl:10197/2616
Keywords: 330; Intelligence; Measurement error; International comparisons